Serum hemoglobin concentration and risk of renal function decline in early stages of diabetic kidney disease: a nationwide, biopsy-based cohort study. Issue 3 (24th May 2021) - Yamanouchi, Masayuki; Furuichi, Kengo; Shimizu, Miho; Toyama, Tadashi; Yamamura, Yuta; Oshima, Megumi; Kitajima, Shinji; Hara, Akinori; Iwata, Yasunori; Sakai, Norihiko; Oba, Yuki; Matsuoka, Shusaku; et al.
Abstract: Background: Prognosticating disease progression in patients with diabetic kidney disease (DKD) is challenging, especially in the early stages of kidney disease. Anemia can occur in the early stages of kidney disease in diabetes. We therefore postulated that serum hemoglobin (Hb) concentration, as a reflection of incipient renal tubulointerstitial impairment, can be used as a marker to predict DKD progression. Methods: Drawing on nationally representative data of patients with biopsy-proven DKD, 246 patients who had an estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 at renal biopsy were identified: age 56 (45–63) years; 62.6% men; Hb 13.3 (12.0–14.5) g/dL; eGFR 76.2 (66.6–88.6) mL/min/1.73 m 2 ; urine albumin-to-creatinine ratio 534 (100–1480) mg/g Crea. Serum Hb concentration was divided into quartiles: ≤12, 12.1–13.3, 13.4–14.5 and ≥14.6 g/dL. The association between serum Hb concentration and the severity of renal pathological lesions was explored. A multivariable Cox regression model was used to estimate the risk of DKD progression (new onset of end-stage kidney disease, 50% reduction of eGFR or doubling of serum creatinine). The incremental prognostic value of DKD progression by adding serum Hb concentration to the known risk factors of DKD was assessed. Results: Serum Hb levels negatively correlated with all renal pathological features, especially with the severity of interstitial fibrosis ( ρ = −0.52; P < 0.001). During a median follow-up of 4.1 years, 95 developed DKD progression. Adjusting for known risk factors of DKD progression, the hazard ratio in the first, second and third quartile (the fourth quartile was reference) were 2.74 [95% confidence interval (CI) 1.26–5.97], 2.33 (95% CI 1.07–5.75) and 1.46 (95% CI 0.71–3.64), respectively. Addition of the serum Hb concentration to the known risk factors of DKD progression improved the prognostic value of DKD progression (the global Chi-statistics increased from 55.1 to 60.8; P < 0.001). Conclusions: Serum Hb concentration, which reflects incipient renal fibrosis, can be useful for predicting DKD progression in the early stages of kidney disease. Graphical Abstract: